2013
DOI: 10.1096/fj.12-223982
|View full text |Cite
|
Sign up to set email alerts
|

15‐Epi‐lipoxin A 4 inhibits human neutrophil superoxide anion generation by regulating polyisoprenyl diphosphate phosphatase 1

Abstract: Regulation of leukocyte activation is critical to limit unintended tissue injury during acute inflammation. On neutrophil activation, polyisoprenyl diphosphate phosphatase 1 (PDP1) rapidly converts presqualene diphosphate to presqualene monophosphate to facilitate cell activation. Lipoxins are potent anti-inflammatory mediators for neutrophils, yet their counterregulatory signaling mechanisms remain to be determined. 15-Epi-lipoxin A4 (15-epi-LXA4) blocked agonist-initiated association of the nicotinamide aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…In ex vivo studies, LXA 4 had no effect on PMA stimulated neutrophil free radical generation in CLP cells. The variability in free radical production between different studies may be related to the number of platelets in the preparation as LXA 4 reduction in free radical production is dependent on neutrophil-platelet interaction [49]. Taken together with in vivo data, the results support the notion that LXA 4 did not cause excessive neutrophil free radical formation in sepsis.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In ex vivo studies, LXA 4 had no effect on PMA stimulated neutrophil free radical generation in CLP cells. The variability in free radical production between different studies may be related to the number of platelets in the preparation as LXA 4 reduction in free radical production is dependent on neutrophil-platelet interaction [49]. Taken together with in vivo data, the results support the notion that LXA 4 did not cause excessive neutrophil free radical formation in sepsis.…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, excessive neutrophil derived free radical production has been implicated in tissue injury in several inflammatory conditions [4,5]. The effects of LXA 4 on neutrophil respiratory burst is highly variable, where there are studies which report no change in free radical production in human neutrophils after fMLP stimulation [6,29], and also a decrease [48,49]. Our results showed that CLP only rats had lower blood neutrophil free radical production compared to sham controls while in vivo LXA 4 administration did not significantly affect PMA stimulated free radical production compared to CLP.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Carlo and colleagues demonstrates inhibition of agonist-induced assembly of NADPH oxidase complex by eLXA 4 and inhibition of superoxide anion generation by human neutrophils (14).…”
Section: Clinical Relevancementioning
confidence: 99%
“…One intracellular signaling mechanism for SPM regulation of cellular responses in human neutrophils is via receptor-mediated inhibition of protein kinase C – βII (PKCβII) phosphorylation and activation of polyisoprenyl diphosphate phosphatase 1 (PDP1), a pivotal phosphatase for polyisoprenyl diphosphate remodeling (131). Polyisoprenyl phosphates are present in resting cell membranes.…”
Section: Spm Display Cell Type Specific Actionsmentioning
confidence: 99%
“…The phosphatase responsible for the rapid conversion of PSDP to PSMP was recently identified as PDP1 (135, 136). Both PSDP and PDP1 are present in human neutrophils (132, 136), and when neutrophils are activated by soluble pro-inflammatory stimuli, there is an increase in phospho-PKCβII (131) that can phosphorylate PDP1 and lead to PSDP conversion to PSMP, facilitating NADPH oxidase assembly and other functional responses (131). In contrast, the SPM 15-epi-LXA 4 interacts with ALX/FPR2 receptors to block agonist-triggered PKCβII phosphorylation and subsequent PDP1 activation, leading to increased availability of PSDP that restrains cellular pro-inflammatory responses (131).…”
Section: Spm Display Cell Type Specific Actionsmentioning
confidence: 99%